RESEARCH OF THE MOTIVATIONAL MENTAL STATES OF FUTURE BACHELORS OF THE FACULTY OF PHYSICAL EDUCATION AND SPORTS IN THE EDUCATIONAL PROCESS - Popovych, Ihor; Halian, Olena; Bokhonkova, Yuliia; Serbin, Iyuriy; Buhaiova, Nataliia; Blyskun, Olena; Yaremchuk, Vitaliya (Revista Inclusiones, 2020)
The purpose of the article is to research the motivational mental states of future bachelors of the Faculty of Physical Education and Sports, majoring in “Secondary Education (Physical Education)” and “Physical Education and Sports”. Motivational mental states are important regulators of educational, professional, sports, competitive activity of bachelors. Educators’ understanding of motivational mental states makes it possible to operationalize the tasks of educational and professional training of future Physical Education teachers and professional athletes. The research represents tests with standardized questionnaires and factor analysis of bachelor’s motivational mental states (n=232). The structure of motivational mental states is determined by factor analysis. Factor 1 “Cognitive ego-motivation” (24.28%) and Factor 3 “Analytical and synthetic” (9.99%) were found to be the main ones. The results obtained may be of interest to the heads of sports educational establishments that organize the educational process of bachelors, coaching staff, athletic directors, anyone involved in the education and training of bachelors-teachers of Physical Education, bachelors-athletes, as well as researchers of psychology and physical education.